The role of the family in the context of the psychological well-being of the oncologically ill person - Agnieszka Nymś-Górna (Kazimierz Wielki University, 2017)
It will be shown how valuable the cancer is to support the family, friends and wider society. From the psycho-oncology I will present forms of support and ways to cope with the difficulties (including emotional). It will be very important to show difference kind of barriers in life of oncologically ill people and theirs families.